The Role of Media in Building Social Tolerance in Kyrgyzstan’s Ethno-Cultural Diversity - Akmatbekova Zhanara; Duishekeeva Aina; Baizakova Nurzat; Amatova Gulzina; Fangxin Hu (Open Cultural Studies)
This study investigates the extent to which Kyrgyz media influence public perceptions of ethno-cultural diversity and contribute to either tolerance or conflict. It identifies a significant correlation between media narratives and societal attitudes, demonstrating that the language, tone, and framing of media coverage can both foster inter-ethnic harmony and amplify social tensions. The methodology includes content analysis of materials from various media, such as television, online resources, and other media, from January to August 2024. The focus is on inter-ethnic relations, representations of ethnic groups, language and rhetoric of publications, and audience reactions. The study determined that the Kyrgyz media is dominated by materials aimed at supporting cultural diversity and inter-ethnic interaction, but there are also negative publications focusing on conflicts and migrant problems. Most of the positive materials focused on covering cultural events and ethnographic expeditions. A significant difference in content and influence between online media and television was noted: television is more inclined to neutral and positive coverage, while online media are more likely to focus on problems and conflicts. The study confirms the importance of the media in shaping public perceptions of ethnic and cultural diversity and emphasises the need to support positive and neutral materials that promote inter-ethnic tolerance in Kyrgyzstan.